2022
DOI: 10.1055/a-1925-6494
|View full text |Cite
|
Sign up to set email alerts
|

Can Hypoxia Alter the Anaerobic Capacity Measured by a Single Exhaustive Exercise?

Abstract: The present study aimed to compare the MAODALT in situations of hypoxia and normoxia to confirm the method validity. Seventeen healthy and physically active men participated in this study, aged 25.2 ± 3.2 years. All participants underwent four days of evaluation. The first day was performed a body composition test, an incremental test to exhaustion to determine the maximum oxygen uptake, familiarizing the hypoxia (H) and normoxia (N) situation and the equipment used. On the second, third and fourth days, supra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Additionally, the AC [La-]+PCr is significantly correlated with 30-s Wingate mean (r = 0.79) and peak (r = 0.78) power output [13], swimming performances from 50 to 400 meters (r = 0.68 to 0.91) [14], and performance outcomes derived from the 30-s tethered running (mean force: r = 0.79) [15]. Recently, it was also verified that AC [La-]+PCr remains unchanged under reduced O 2 conditions (i.e., hypoxia), reinforcing its validity as an anaerobic index [16].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the AC [La-]+PCr is significantly correlated with 30-s Wingate mean (r = 0.79) and peak (r = 0.78) power output [13], swimming performances from 50 to 400 meters (r = 0.68 to 0.91) [14], and performance outcomes derived from the 30-s tethered running (mean force: r = 0.79) [15]. Recently, it was also verified that AC [La-]+PCr remains unchanged under reduced O 2 conditions (i.e., hypoxia), reinforcing its validity as an anaerobic index [16].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…After the TTF 100 (AC [La-]+PCr 100) and TTF 110 (AC [La-]+PCr 110), the anaerobic contributions were estimated by the AC [La-]+PCr method [8], calculated as the sum of oxygen equivalents from the phosphagen (E PCr ) and the glycolytic/lactic metabolism (E [La-] ). The E PCr was attributed to the EPOC fast area [8,31], calculated as the product between the first amplitude (A 1 ) and time constant (τ 1 ) extracted after a bi-exponential fitting model (Equation 1) of the VȮ 2 and the recovery time (10 min) [16] (OriginPro 8.5, Microcal, MA, USA).…”
Section: Energy System Contributionsmentioning
confidence: 99%
“…Additionally, the use of EPOC and lactate production to estimate anaerobic contribution were used in indoor rock climbing [22], high-intensity intermittent efforts [26], and goalball [27]. It has also been shown that MAOD alt , unaffected by oxygen availability (i.e., hypoxia) [28], is modified by high-intensity intermittent training associated with hypoxia during rest inter-effort [29], and by maturation levels [23] and detects changes from sodium bicarbonate [30], but not after 6-week beta-alanine supplementation [31]. Thus, it can provide greater effectiveness in training strategies and nutritional management to improve health and athletic performance [20].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Em uma amostra do sexo feminino, alguns fatores devem ser levados em consideração. As flutuações hormonais presentes em mulheres de ciclo ovarianos endógenos, podem gerar influências diretas e indiretas no desempenho De Carvalho et al, 2022). No presente estudo, tais variações foram minimizadas, pois as avaliações ocorreram em mesmo período do ciclo menstrual para ambos os grupos.…”
Section: Terapia Por Fotobiomodulaçãounclassified